Use of sugar cane bagasse ash in ultra-high performance concrete (UHPC) as cement replacement. (24th January 2022) - Wu, Nengsen; Ji, Tao; Huang, Ping; Fu, Tengfei; Zheng, Xiaoyan; Xu, Qing
Highlights: Eco-friendly UHPC containing sugar cane bagasse ash (SCBA) was developed. The compressive strength of UHPC containing SCBA almost unchanged. The workability of UHPC containing SCBA improves notably. The autogenous shrinkage of UHPC containing SCBA decreases remarkably. Abstract: Sugar cane bagasse ash (SCBA) is the final waste material in the sugar production chain. Due to the pozzolanic characteristic and the abundance, SCBA has been tried to utilized in construction materials. In this study, ecofriendly ultra-high performance concrete (UHPC) was developed with SCBA as a cement replacement. The effects of SCBA on the fluidity, setting time, compressive strength, flexural strength and autogenous shrinkage of UHPC were analyzed. Hydration heat evaluation, X-ray diffraction (XRD), thermogravimetric (TG) analysis, and mercury injection (MIP) were applied to reveal the effects of SCBA on cement hydration, hydration products and pore structure. The results indicate that the application of SCBA in UHPC as a cement replacement not only maintains the compressive strength but also improves the workability and decreases the autogenous shrinkage of UHPC paste. Compared to the control group, UHPC prepared at a 40% replacement rate obtained a good comprehensive performance. Autogenous shrinkage decreased by 24.48%, and the compressive strength was almost the same as that of the control group. This study verifies the technical feasibility of SCBA application as a cement replacement in UHPC and may further promote the utilization of agricultural byproducts in cementitious materials.